Lymphoid/neuronal cell surface OX2 glycoprotein recognizes a novel receptor on macrophages implicated in the control of their function. - Wright, G; Puklavec, M; Willis, A; Hoek, R; Sedgwick, J; Brown, M; Barclay, N (2000)
The OX2 membrane glycoprotein (CD200) is expressed on a broad range of tissues including lymphoid cells, neurons, and endothelium. We report the characterization of an OX2 receptor (OX2R) that is a novel protein restricted to cells of the myeloid lineage. OX2 and its receptor are both cell surface glycoproteins containing two immunoglobulin-like domains and interact with a dissociation constant of 2.5 microM and koff 0.8 s(-1), typical of many leukocyte protein membrane interactions. Pervanandate treatment of macrophages showed that OX2R could be phosphorylated on tyrosine residues. Blockade of the OX2-OX2R interaction with an OX2R mAb exacerbated the disease model experimental allergic encephalomyelitis. These data, together with data from an OX2-deficient mouse (R. M. Hoek et al., submitted), suggest that myeloid function can be controlled in a tissue-specific manner by the OX2-OX2R interaction.